2005
DOI: 10.1007/s00401-005-1081-x
|View full text |Cite
|
Sign up to set email alerts
|

Transition of areas of eosinophilic neurons and reactive astrocytes to delayed cortical infarcts after transient unilateral forebrain ischemia in Mongolian gerbils

Abstract: The fate of postischemic tissues containing eosinophilic neurons (ENs), whether they remain viable or evolve into infarction, is largely unknown. We analyzed the time profile and distribution of ENs, reactive astrocytes (RAs), and infarction after transient cerebral ischemia. Unilateral forebrain ischemia was induced in Mongolian gerbils by two 10-min unilateral common carotid artery occlusions with a 5-h interval, and the brains at 24 h, 4 days, and 2, 4, and 16 weeks were prepared for morphometric analysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 22 publications
2
21
0
Order By: Relevance
“…While the infarct volume per se did not change at 7-days poststroke, the FJC-positive cell population significantly decreased compared to the pattern observed at 24 or 48 h. After stroke, in brain tissue stained with H & E, degenerating cells becomes eosinophilic and areas of high eosinophilic positive cells evolve into infarcts (Sun et al, 2006). The goal of this staining is to allow a macroscopic differentiation between damaged and undamaged tissue (Garcia et al, 1993).…”
Section: Discussionmentioning
confidence: 93%
“…While the infarct volume per se did not change at 7-days poststroke, the FJC-positive cell population significantly decreased compared to the pattern observed at 24 or 48 h. After stroke, in brain tissue stained with H & E, degenerating cells becomes eosinophilic and areas of high eosinophilic positive cells evolve into infarcts (Sun et al, 2006). The goal of this staining is to allow a macroscopic differentiation between damaged and undamaged tissue (Garcia et al, 1993).…”
Section: Discussionmentioning
confidence: 93%
“…Eosinophilic neurons (EN) are the hallmarks of ischemic encephalopathy [16]. Sun et al [12] reported that intense EN areas transform into infarct areas when compared to areas of low-density EN. In our study, IR group revealed a large number of EN compared to Ebselen and control group.…”
Section: Discussionmentioning
confidence: 99%
“…Total (Cu/Zn and Mn) SOD (EC 1.15.1.1) activity was determined based on the method of Sun et al [12]. The principle of the method is based on the inhibition of Nitro Blue Tetrazolium (NBT) reduction by the xanthine-xanthine oxidase system as a superoxide generator.…”
Section: Determination Of Superoxide Dismutase Activitymentioning
confidence: 99%
“…Eosinophilic neurons (EN) are the hallmarks of ischemic encephalopathy. Sun et al [30,31] reported that intense EN areas transform into infarct areas when compared to areas of low-density EN. They added that low-density EN areas remained as areas of selective neuronal death.…”
Section: Discussionmentioning
confidence: 99%